Are Scale Economies in Banking Elusive or Illusive? - Joseph P. Hughes; Loretta J. Mester; Choon-Geol Moon (Rutgers University, Department of Economics, 2000)
This paper explores how to incorporate banks' capital structure and risk-taking into models of production. In doing so, the paper bridges the gulf between (1) the banking literature that studies moral hazard effects of bank regulation without considering the underlying microeconomics of production and (2) the literature that uses dual profit and cost functions to study the microeconomics of bank production without explicitly considering how banks' production decisions influence their riskiness. Various production models that differ in how they account for capital structure and in the objectives they impute to bank managerscost minimization versus value maximizationare estimated using U.S. data on highest-level bank holding companies. Modeling the bank's objective as value maximization conveniently incorporates both market-priced risk and expected cash flow into managers' ranking and choice of production plans. Estimated scale economies are found to depend critically on how banks' capital structure and risk-taking is modeled. In particular, when equity capital, in addition to debt, is included in the production model and cost is computed from the value-maximizing expansion path rather than the cost-minimizing path, banks are found to have large scale economies that increase with size. Moreover, better diversification is associated with larger scale economies while increased risk-taking and inefficient risk-taking are associated with smaller scale economies.
Keywords: D20; D21; G21; 330; banking; risk; scale economies